Promising Effect of High Dose Ambroxol Treatment on Neurocognition and Motor Development in a Patient With Neuropathic Gaucher Disease 2 - Aries, Charlotte; Lohmöller, Benjamin; Tiede, Stephan; Täuber, Karolin; Hartmann, Guido; Rudolph, Cornelia; Muschol, Nicole (Frontiers in Neurology, 2022)
Gaucher Disease (GD) 2 is a rare inherited lysosomal disorder. Early-onset and rapid progression of neurovisceral symptoms lead to fatal outcome in early childhood. Treatment is symptomatic, a curative therapy is currently not available. This prospective study describes the clinical and biochemical outcome of a GD 2 patient treated with high dose ambroxol from the age of four months. Due to progressive hepatosplenomegaly additional enzyme replacement therapy was required one year after ambroxol monotherapy was initiated. Detailed clinical follow-up data demonstrated an age-appropriate neurocognitive and motor development but no clear benefit on peripheral organs. Glucosylsphingosine (Lyso-GL1) in cerebrospinal fluid decreased remarkably compared to pre-treatment, whereas Lyso-GL1 and chitotriosidase in blood increased. Ambroxol treatment of patient fibroblasts revealed a significant increase in β-glucocerebrosidase activity in vitro. To our knowledge, this is the first report of a GD 2 patient with age-appropriate cognitive and motor development at 3 years of age. Combination of high dose ambroxol with ERT proved to be a successful approach to manage both visceral and neurological manifestations.